PENGEMBANGAN MODEL ADOPSI TEKNOLOGI INFORMASI TERHADAP MODEL PENERIMAAN TEKNOLOGI DIANTARA UMKM - Asrul Sani; Ninuk Wiliani; Agus Budiyantara; Nur Nawaningtyas (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
This study is preliminary in the development of a new model whereby combining and integrating an existing model, the adoption model of information technology with the technology acceptance model. The development of this model is done by using the logic of the IPO (input-process-output) and the causal model by combining, adopting, and adapting the previous model. The effect of the formed path consists of 16 links and produces 11 variables. The existing variables will be formed into 55 indicators, where one variable creates five indicators. The process of developing this model will assist researchers in testing the information technology adoption model and the technology acceptance model so that it will get the effect that occurs in both models. This research will also contribute to further research, especially in the study of information systems, which will provide a theoretical basis for modeling. Besides, the transparency of the development and proposed models, especially in the instruments used, will be taken into consideration in conducting further research .